Comparison of right-to-left shunt characteristics in cryptogenic embolic ischemic stroke and non-cardioembolic ischemic stroke - Scavasine, Valeria Cristina; Chamma, Jamileh Ferreira; Bazan, Rodrigo [UNESP]; Braga, Gabriel Pereira; Lange, Marcos Christiano; de Hiroki Flumignan Zétola, Viviane (FapUNIFESP (SciELO), 2021)
Background: Patent foramen ovale (PFO) has been considered a potential mechanism of embolic stroke of undetermined origin. Objective: The aim of the present study was to identify the features of the right-to-left shunt (RLS) in patients with undetermined embolic ischemic stroke and compare them with those of patients with non-cardioembolic ischemic stroke. Methods: A retrospective study was conducted with 168 patients with stroke and RLS separated into the following two groups: the undetermined embolic stroke group (UES group) and non-cardioembolic stroke group (NCES group). All patients were assessed by transcranial Doppler to evaluate the presence and quantification of microembolic signals (MES) at rest and under Valsalva maneuver. Results: Of all patients evaluated in the current study, 96 were included in the UES group and 72 in the NCES group. In the UES group, 65 patients had RLS with ≥10 MES (67.7%), which was higher than that observed in the NCES group (51.4%, p=0.038). According to the moment of the cardiac cycle, 75 patients (78.1%) in the UES group had a positive test at rest compared to 42 (58.3%) in the NCES group (p=0.007). Conclusions: The current study demonstrated that almost 70% of patients with undetermined embolic stroke and PFO presented a large RLS and more than 75% had RLS at rest. These findings suggest that the size of the shunt should be taken into account when evaluating whether PFO could be a possible mechanism underlying cryptogenic stroke.
Comparação das características do shunt direita-esquerda em pacientes com AVC isquêmico criptogênio e AVC não cardioembólico
Keywords: Doppler; Embolism; Foramen ovale; Ischemic stroke; Paradoxical; Patent; Stroke; Transcranial; Ultrasonography